Local Probing of a Superconductor's Quasiparticles and Bosonic Excitations with a Scanning Tunnelling Microscope - Gozlinski, Thomas (Experimental Condensed Matter Physics, 2023)
Complementary to scattering techniques, scanning tunnelling microscopy provides atomic-scale real space information about a material's electronic state of matter. State-of-the-art designs of a scanning tunnelling microscope (STM) allow measurements at millikelvin temperatures with unprecedented energy resolution. Therefore, this instrument excels in probing the superconducting state at low temperatures and especially its local quasiparticle excitations as well as bosonic degrees of freedom.